THE IMPACT OF CLINICAL PATHWAY TO EFFECTIVENESS OF PATIENT CARE IN CURRENT MEDICAL PRACTICE IN HOSPITAL: A LITERATURE REVIEW - Rovels Agber Maywell Iroth; Anhari Achadi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Clinical pathway is an effective way to maximize patient outcomes by organize and standardize care processes. Clinical pathway bring impact to the patient treatment and the quality of care in hospital. This study aims to examine the impact of clinical pathway in effectiveness of patient treatment in hospital. Methods: This study was a literature review used PRISMA guidelines. Data obtained from electronic journal database ProQuest that published from January to December 2018 and used English or Indonesia language. The keywords of clinical pathway, care pathway, length of stay and mortality had been used to find relevant journal. Results: The search of electronic journal database found 1,937 articles. Articles that were not suitable with inclusion criteria must be excluded. Totally, 6 articles were relevant for this study. The 6 articles were conducted in USA, Belgium, Australia, India, and China. The analyzed from these articles showed that clinical pathway gave positive impact to the length of stay and patient outcome in the hospital if the resources of the hospital were ready to implement clinical pathway. Conclusion: Clinical pathway reduced the length of stay, improved the patient outcome, and reduced the mortality rate in hospital. To get the maximum benefit for implementing clinical pathway, the hospital must be prepared the environment and resources first before implementing clinical pathway. Keywords: clinical pathway, care pathway, patient outcome, length of stay